Analisis Kasus Overmacht dan Pemutusan Kontrak Sepihak: Studi Putusan Nomor 672k/Pdt/2020 antara CV. Berlian Mas dan Pemerintah Daerah Kabupaten Trenggalek - Salwa, Rachel Amanda; Chandra, Restia Delya Ayu; Ilzan, Safa Aqila; Athareza, Sultan; Sentosa, Ummu Hani; Rizkianti, Wardani (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The dispute between CV. Berlian Mas and the Regional Government of Trenggalek Regency, as reflected in Supreme Court Decision No. 672 K/Pdt/2020, stemmed from delays in the Plapar Bridge construction project, which the contractor attributed to flooding as a form of force majeure (overmacht). Although the contractor requested an extension of time, the regional government unilaterally terminated the contract without complying with the notification procedures required under the contract and procurement regulations. An assessment of Articles 1244–1245 of the Indonesian Civil Code shows that the flood did not objectively qualify as force majeure due to insufficient formal evidence and inadequate mitigation. The Supreme Court ruled that the termination constituted a breach of contract (wanprestasi), not a tort. This decision highlights the importance of strict proof of force majeure, adherence to the principle of pacta sunt servanda, and procedural compliance within government procurement contracts.